Interpersonal relationship between the mentor and mentee in clinical nursing practice - Nastran, Ana (Obzornik zdravstvene nege, 2023)
Introduction: The interpersonal relationship between the nurse mentor and the mentee (i.e., student nurse) is critical to the success of the mentoring process and training of new nurses. The aim of this study was to examine and explore the interpersonal relationships between nurse mentors and their mentees and to identify the factors that influence their relationship.Methods: A qualitative approach with a descriptive-interpretive design was used for data collection and analysis. Semi-structured interviews were conducted on a purposive sample of mentors and two focus groups with mentees – student nurses. Four mentors and eight mentees were involved in the study. Data were collected in December 2021 and analysed using content analysis.Results: Mentors and mentees had relatively similar perceptions of their interpersonal relationship. We identified the common main theme "Mentor-Mentee Interpersonal Relationship", and two subthemes, namely "Characteristics of the Mentor-Mentee Interpersonal Relationship" and "Factors Influencing the Mentor-Mentee Interpersonal Relationship". Both mentors and mentees were found to have consistent expectations regarding their role in clinical practice. The most important factors of their interpersonal relationship reported by both mentors and mentees were the personality traits of mentors and mentees, the setting of boundaries in their interpersonal relationship, the amount of time required to establish the interpersonal relationship, and differences in the relationship depending on the domain of clinical practice.Discussion and conclusion: The study identifies the key characteristics and factors of the interpersonal relationship between the mentor and mentee in the mentoring process. It highlights the key elements that all those involved in clinical practice need to be aware of in order to overcome various potential barriers and improve the mentoring experience in the clinical setting.
Keywords: clinical practice; faculties; fakulteta; health system; klinično usposabljanje; mentoring; mentoriranje; nursing students; študenti; zdravstveni sistem